Role of ultrasonography in the evaluation of cause of shoulder pain - Modak, Aditi; Rahman, Sonia; Mohiuddin, Abu S. (International Journal of Research in Medical Sciences, 2022)
Background: Painful shoulder is one of the more common patient problems. Most of the time patients, complaining of chronic or even acute pain at shoulder area, are found normal with x-ray. Aim of this study was to evaluation of cause of shoulder pain using ultrasonography of shoulder joint. Methods: This cross sectional observational study was carried out in the department of Radiology and Imaging, BIRDEM for the period of 1st June 2008 to 30th May 2009. Total 37 patients were included in the study. Accidental case, referred shoulder pain and shoulder pain due to systemic causes were excluded. Every patient underwent physical examination, x-ray and ultrasonography for further evaluation. Ethical approval was taken from institutional review board. Statistical analysis was done for validation of x-ray and USG in the diagnosis of shoulder pain. Results: The mean±SD age was 46.14±10.85 years and all patients were within 28 to 70 years age range. Sensitivity of USG to diagnose different type of shoulder pathology was 93.3%, specificity 54.5%, positive predictive value 58.3%, negative predictive value 92.3% and accuracy 70.3 whereas Sensitivity of x-ray to diagnose different type of shoulder pathology was 13.3%, specificity 90.9%, positive predictive value 50.0%, negative predictive value 60.6% and accuracy 59.5%. Conclusions: USG is a sensitive and accurate imaging modality for evaluating the cause of shoulder pain.